“The People Who Stayed”: Back River Memorial Gardens Cemetery as a Site of Jewish Migrant and Montreal Urban Meaning-Making - Frost, Naomi; Sheftel, Anna (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Ahuntsic; Cimetières; Juifs

Sanctuary in pieces: two centuries of flight, fugitivity, and resistance in a North American city - Madokoro, Laura (2024)

Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

Remembering the Duvalier era: Resistance, Exile, and Solidarity in the Life Stories of Haitian-Montrealers - Riou, Geneviève (Université Concordia, 2022)
Keywords: Haïtiens

Qui a le droit d’entrer et de rester au Canada? Quand ces questions s’invitent chez les Franco-Québécoises (1946-1955) - Trimble, Sheena (Études canadiennes / Canadian Studies, 2022)
Keywords: Femmes

Dal Mediterraneo all’Atlantico: ricordi di migrazione nella Montréal del secondo dopoguerra - Piraro, Sergio (Italian Canadiana, 2021)
Keywords: Italiens

Idealized Spaces, Internationalized Selves: Japanese Migration to Montreal, Canada, 1990-Present - Tabakow, Elizabeth (Université Concordia, 2021)
Keywords: Japonais

Histoire des communautés noires au Québec et à Montréal (3e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-23-00
Keywords: Haïtiens; Noirs

The Montreal Shtetl: Making Home After the Holocaust - Abramson, Zelda; Lynch, John (Between the Lines, 2019)
Keywords: Famille; Juifs; Travail

Les hommes d'Église français dans la migration vers le Canada, 1842-1914 - Balloud, Simon (Université de La Rochelle et Université du Québec à Montréal, 2019)
Keywords: Communautés religieuses; Français

La langue française chez les Sépharades du Québec: une stratégie de préservation culturelle et d'intégration sociale (1960-1980) - Chevalier-Caron, Christine; Cohen, Yolande (Revue d'histoire de l'éducation / Historical Studies in Education, 2019)
issued: 2019-21-00
Keywords: Commission des écoles catholiques de Montréal; Francophones; Juifs; Langue; Maghrébins; Marocains

Mille nuances pour un pays - Corriveau, Jeanne (Continuité, 2019)
issued: 2019-24-00
Keywords: Chinois; Conservation; Italiens; Patrimoine; Syriens

L'impact des immigrants français dans l'enseignement à Montréal, 1880-1914: le cas de la CÉCM et de Polytechnique - Gagnon, Robert (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Commission des écoles catholiques de Montréal; Français; École polytechnique

La migration des enseignants religieux français au Québec de 1900 à 1914 - Hélou, Guillaume (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Communautés religieuses; Enseignants; Français

Les artistes français au Canada et au Québec - Lacroix, Laurier (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Français

Témoins discrets - Leclerc, Jean-François (Continuité, 2019)
issued: 2019-24-00
Keywords: Chinois; Grecs; Irlandais; Italiens; Juifs; Noirs; Patrimoine; Syriens

Les Québécois d'origine italienne. Une longue histoire - Linteau, Paul-André (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Italiens

Contre l'immigration française au Canada? L'alliance du Consulat général et de la Chambre de commerce française à Montréal (1893-1914) - Martinetti, Brice (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Chambre de commerce française; Consulat général de France; Français

À la ville, à la scène, l'impact fondateur des immigrants français - Olson, Sherry (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Français; Théâtre

Une communauté singulière. Les Pesaresi de Montréal - Perin, Roberto (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Italiens

Bienvenue dans la Petite-Italie de Montréal - Taschereau, Sylvie (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Les Italo-Montréalais [sic] et leur histoire (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
issued: 2019-22-00
Keywords: Italiens; Travail

Les Italo-Montréalais [sic] et leur histoire (suite et fin) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
issued: 2019-23-00
Keywords: Guerre; Idéologies; Italiens

De la Toscane au Canada, les statuaires italiens - Tremblay, Marc Alain; Carli-Trudeau, Jocelyne F. (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Arts sacrés; Italiens; Sculpture

Les communautés culturelles du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-22-00
Keywords: Allemands; Députés; Godin; Gérald; Grecs; Irlandais; Itinérance; Johns; Emmett (Père Pops); Juifs; Plateau Mont-Royal; Portugais; Poésie; Quartiers; Roumains

"My Love, How Different Life Is Here..." A Young Italian Woman's Impressions of Postwar Montreal - Cancian, Sonia (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Femmes; Italiens; Langue; Travail

Moving into the World of Work. Youth Today and a Century Ago - Castel, Frédéric; Olson, Sherry (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Enfants; Famille; Mobilité résidentielle; Navettage; Travail

Établissement et stratégies d'intégration des immigrants syriens à Montréal, 1890-1945 - Djahnine, Yasmine (Université du Québec à Montréal, 2018)
Keywords: Syriens

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Building and Reshaping the Suburban Landscape: The Role of Immigrant Communities - Germain, Annick; Rose, Damaris; Richard, Myriam (Montreal: The History of A North American City, 2018)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Permanence et renouvellement des familles ouvrières: le cas du Village-aux-Oies et de la rue Forfar, 1901-1921 - Giguère, Charles-Robert (Université du Québec à Montréal, 2018)
Keywords: Famille; Locataires; Logement; Mobilité résidentielle; Villages

L'histoire de la vie de réfugiés montréalais. Une rencontre - High, Steven (Les Presses de l'Université Laval, 2018)
Translators: _:n54292
Keywords: Histoire

"Miami": The Cuban Diasporas in Toronto and Montreal - Krull, Catherine; Stubbs, Jean (Other Diplomacies, Other Ties. Cuba and Canada in the Shadow of the US, 2018)
Keywords: Cubains

De l'exil à la communauté : une histoire de l'immigration haïtienne à Montréal 1960-1990 - Saint Victor, Alain (Université du Québec à Montréal, 2018)
Keywords: Haïtiens; Travail

Metropolitan Expansion: The Challenge of Polycentricity - Sénécal, Gilles; Vachon, Nathalie (Montreal: The History of A North American City, 2018)
Keywords: Autoroutes; Banlieue; Centres commerciaux; Mobilité résidentielle; Métropole

À la croisée de la Révolution tranquille et du judaïsme orthodoxe: L'implantation de la communauté hassidique des Tasher au cœur du Québec francophone et catholique (1962-1967) - Lacasse, Simon-Pierre (Histoire sociale / Social History, 2017)
Number: 102
Keywords: Juifs

Histoire des Juifs du Québec - Anctil, Pierre (Boréal, 2017)
Keywords: Juifs

Ruptures et continuités dans la représentation de l'immigration. Une analyse préliminaire du journal Le Devoir (1910-1963) - Anctil, Pierre (Revue Anthropologie et Sociétés, 2017)
Number: 3
Keywords: Devoir (Le); Francophones; Nationalisme

La construction d'une mémoire commune - Bérubé-Sasseville, Olivier (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Groupes populaires; Juifs; Maghrébins; Marocains

Les sépharades dans les études démographiques - Burgard, Antoine (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Juifs; Maghrébins; Marocains; Recensements

Le Quartier chinois au centre-ville de Montréal. Le processus de construction d'un quartier - Cha, Jonathan (Montréal : la cité des cités, 2017)
Keywords: Chinois; Quartier chinois; Quartiers; Tourisme

De l'Alliance israélite universelle à l'école Maïmonide - Chevalier-Caron, Martin (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Commission des écoles catholiques de Montréal; Juifs; Maghrébins; Marocains

Les sépharades du Québec. Parcours d'exils nord-africains - Cohen, Yolande (Del Busso, 2017)
Keywords: Juifs; Maghrébins; Marocains

Edmond Fournier, charpentier-menuisier à Montréal (1876-1946): la petite histoire d'une famille ouvrière sur des cartes postales - Fournier, Louis (Histoire Québec, 2017)
Number: 3
Keywords: Charpentiers; Famille; Menuisiers; Travail

Crises identitaires entre laïcité et orthodoxie - Lapidus, Steven (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Juifs; Maghrébins; Marocains

Les hassidims dans la ville : regard sur la cohabitation - Lapidus, Steven (Vivre ensemble à Montréal : épreuves et convivialités, 2017)
Keywords: Juifs

Montréal, foyer principal des Français du Canada - Linteau, Paul-André (Transposer la France: l'immigration française au Canada (1870-1914), 2017)
Keywords: Français

Un jurassien en Amérique du Nord: de Cornol à Montréal, le journal d'Amédée Girard (1893-1897) - Lovis, Marie-Angèle (Presses de l'Université de Montréal, 2017)
Keywords: Suisses

Juifs marocains à Paris et à Montréal - Messika, Martin; Cohen, Yolande (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Juifs; Maghrébins; Mariage; Marocains; Travail

L'emploi des femmes judéo-marocaines à leur arrivée à Montréal (1956-1978) - Néméh-Nombré, Philippe (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Femmes; Juifs; Maghrébins; Marocains; Travail

Mapping Work in Early Twentieth-Century Montreal: A Rabbi, a Neighbourhood, and a Community - Poutanen, Mary Anne; Gilliland, Jason (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-21-00
Keywords: Famille; Juifs; Travail

La position des centrales syndicales et des organisations patronales à l'égard de l'immigration au Québec, de 1965 à 1995 - Provost-Turgeon, Florence (Université de Montréal, 2017)
Keywords: Chambre de commerce

Le quartier chinois de Montréal à l'aube de nouvelles transformations sociales et spatiales : quelles significations pour les jeunes migrants d'origine chinoise? - Charbonneau, Marie-Ève (Institut national de la recherche scientifique et Université du Québec à Montréal, 2016)
Keywords: Chinois; Quartier chinois; Quartiers

Politiques de l'accueil : États et associations face à la migration des juifs d'Afrique du Nord en France et au Canada des années 1950 à la fin des années 1970 - Messika, Martin (Université du Québec à Montréal et Université Paris I Panthéon-Sorbonne, 2016)
Keywords: Juifs

Histoire de la communauté japonaise du Québec, 1942-1988 - Roy, Christian (Université du Québec à Montréal, 2016)
Keywords: Japonais

Le Congrès juif canadien et l'hostilité à l'immigration juive dans l'immédiat après-guerre (1945-1948) - Burgard, Antoine (Globe: revue internationale d'études québécoises, 2015)
Number: 1
Keywords: Congrès juif canadien; Juifs

Les mots d'une migration postcoloniale dans les récits des Juifs montréalais - Cohen, Yolande; Messika, Martin; Cohen Fournier, Sara (Revue d'histoire de l'Amérique française, 2015)
issued: 2015-22-00/2015-23-00
Keywords: Juifs; Maghrébins; Marocains

La régionalisation de l'immigration au Québec: le débat public entre le gouvernement et la société civile à l'origine de la politique, 1987-2000 - Daneau, Lauréanne (Université du Québec à Trois-Rivières, 2015)

De l'Afrique au Québec: les réseaux missionnaires comme vecteurs d'intégration socio-ecclésiale - Foisy, Catherine (Études d'histoire religieuse, 2015)
Number: 1-2
Keywords: Africains; Communautés religieuses; Missionnaires d'Afrique (Pères blancs); Missions

Préserver et mettre en valeur l'histoire et le patrimoine de l'immigration dans un musée d'histoire: l'expérience du Centre d'histoire de Montréal - Leclerc, Jean-François (Musées, histoire, migrations, 2015)
Keywords: Centre d'histoire de Montréal; Histoire; Musées

«How many is too many»? Le débat public canadien et québécois sur l'arrivée massive des réfugiés indochinois, juin à décembre 1979 - Pagé, Geneviève (Université du Québec à Trois-Rivières, 2015)
Keywords: Cambodgiens; Chinois; Devoir (Le); Montreal Gazette; Montreal Star; Presse (La); Vietnamiens

Oral History at the Crossroads. Sharing Life Stories of Survival and Displacement - High, Steven (University of British Columbia Press, 2014)
Keywords: Histoire

Refugee Narratives in Montreal: Negotiating Everyday Social Exclusion and Inclusion - Manjikian, Lalai (Université McGill, 2014)
Keywords: Théâtre

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

Locating Diasporas: Afro-Caribbean Migrations and the Transnational Dialectics of Race and Community in North America, 1910-1929 - Toney, Jared Glen (University of Toronto, 2014)
Keywords: Africains; Caribéens; Noirs

Quebec, Haiti, and the Deportation Crisis of 1974 - Mills, Sean (Canadian Historical Review, 2013)
Number: 3
Keywords: Haïtiens

L'intégration des immigrants. Cinquante ans d'action publique locale - Fourot, Aude-Claire (Presses de l'Université de Montréal, 2013)

La sociologie urbaine à l’épreuve de l’immigration et de l’ethnicité: de Chicago à Montréal en passant par Amsterdam - Germain, Annick (Sociologie et sociétés, 2013)
issued: 2013-23-00
Keywords: Sociologie

Le parcours de réorientation professionnelle d’immigrantes hautement qualifiées à Montréal: une étude exploratoire - Germain, Danielle (Université de Montréal, 2013)
Keywords: Famille; Femmes; Travail

Les immigrants français à Montréal, agents de transferts culturels (1870-1914) - Linteau, Paul-André (Les échanges culturels internationaux: France, Brésil, Canada-Québec, 2013)
Keywords: Français

Mad Flight? The Montréal Migration of 1896 to Brazil - Zucchi, John (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2013)
Number: 2

Des résistants à Montrealpuram. Implantation et conditions de vie des Québécois d'origine tamoule sri lankaise - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Sri Lankais

Être des battants quand on est abattus. Implantation et conditions de vie des Québécois d'origine congolaise - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Congolais

Un mariage qui aurait tout pour marcher. Implantation et conditions de vie des Québécois d'origine algérienne - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Algériens

Un mémoricide pour mémoire. Implantation et conditions de vie des Québécois d'origine khmère cambodgienne - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Cambodgiens

Enquête sur les relations problématiques entre Français et Québécois francophones - Dupuis, Jean-Pierre (Recherches sociographiques, 2012)
issued: 2012-05/2012-08
Keywords: Francophones; Français

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Les banlieues de l'immigration ou quand les immigrants refont les banlieues - Germain, Annick; Rose, Damaris; Richard, Myriam (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

N'oublie pas, il faut être fier de son origine. Reconstruire et transmettre le bouddhisme cambodgien en contexte migratoire postgénocidaire - Létourneau, Anne (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Cambodgiens

Familiar Faces and Nostalgic Places: Family Photographs as Instruments of Memory and Identity in the Montreal Armenian Community - Nazarian, Vana S. (Université Concordia, 2012)
Keywords: Arméniens; Famille; Photographie

Jeunes Français au Québec: quels modes d’usage des dispositifs d’aide aux nouveaux arrivants? - Papinot, Christian; Le Her, Mélanie; Vilbrod, Alain (Recherches sociographiques, 2012)
issued: 2012-05/2012-08
Keywords: Français

Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration - Rousseau, Louis (Presses de l'Université du Québec, 2012)
Keywords: Africains; Cambodgiens; Maghrébins; Sri Lankais

Expérience migratoire antérieure et déqualification. Étude de cas portant sur des immigrants russophones à Montréal - Vaynman, Irina (Université de Montréal, 2012)
Keywords: Russes; Travail

Immigration et alimentation à Montréal aux XVIIe et XVIIIe siècles: essai d’interprétation à partir d’analyses isotopiques sur des populations archéologiques - Vigeant, Jacinthe (Université de Montréal, 2012)
Keywords: Alimentation

Une continuité reconstruite à partir des ruptures migratoires. Les cas des Juifs argentins immigrés à Montréal pendant la période 2000-2007 - Altminc, Ruth (Université de Montréal, 2011)
Keywords: Argentins; Juifs

Une analyse des déterminants de la mobilité linguistique intergénérationnelle des immigrants allophones au Québec - Bélanger, Alain; Sabourin, Patrick; Lachapelle, Réjean (Cahiers québécois de démographie, 2011)
issued: 2011-21-00
Keywords: Langue

Les jeunes acteurs du développement: étude comparative sur la migration des jeunes adultes dans les métropoles de Montréal (QC-Canada) et Porto Alegre (RS-Brésil) - Brandt, Grazielle (Université du Québec à Chicoutimi et Université du Québec à Rimouski, 2011)
Keywords: Métropole

Vulnérabilité, observance et adhésion thérapeutique: quels risques? La prévention de la tuberculose chez les enfants immigrants à Montréal - Carle, Marie-Ève (Université de Montréal, 2011)
Keywords: Enfants; Hôpital Sainte-Justine; Hôpitaux; Tuberculose

An Irish heart: how a small immigrant community shaped Canada - Doyle Driedger, Sharon (HarperCollins Publishers, 2011)
Keywords: Griffintown; Irlandais; Quartiers

Elephant in the City: Visual Culture and the Aesthetic Elsewhere of Indian Restaurants in Montreal, QC - Herbert, Rhiannon (Université Concordia, 2011)
Keywords: Indiens; Restaurant

German Migrants in Montreal: Uses and Meanings of an Ethnic Category - Storks, Maike (Université Concordia, 2011)
Keywords: Allemands

L’intégration socio-scolaire et les stratégies identitaires d’adolescents iraniens à Montréal - Aghasi-Sorkhabi, Lida (Université de Montréal, 2010)
Keywords: Iraniens

Les rapports entre les francophones et Juifs dans le contexte montréalais - Anctil, Pierre (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Francophones; Juifs

Families, Lovers and their Letters: Italian Postwar Migration to Canada - Cancian, Sonia (University of Manitoba Press, 2010)
Keywords: Famille; Femmes; Italiens

L'accès au logement par les nouveaux arrivants à Montréal: le cas des réfugiés et demandeurs d'asile en provenance d'Afrique subsaharienne - Charette, Alexandra (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2010)
Keywords: Africains; Logement

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Number: 6
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

Migrations juives marocaines au Canada ou comment devient-on sépharade? - Cohen, Yolande (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Juifs; Maghrébins; Marocains

Where Do I Belong? Narratives from the Lives of Iranians in Montreal - Dehghani Estarki, Mahdi (Université McGill, 2010)
Keywords: Iraniens

Vieillir ailleurs: options identitaires et paroles d'aînés d'origine libanaise - El-Hage, Habib (Université du Québec à Montréal, 2010)
Keywords: Libanais

Invisible Migrants: The Case of Russians in Montreal - Gingras, Phillip (Université Concordia, 2010)
Keywords: Russes

Les maux de ventre des enfants haïtiens de Montréal: entre la recomposition culturelle et la souffrance familiale - Gomez Cardona, Liliana (Université de Montréal, 2010)
Keywords: Enfants; Haïtiens

Au cœur des institutions d'immigration: dispositifs, gestion et contrôle migratoire au Canada - Haince, Marie-Claude (Université de Montréal, 2010)

La musique des Chiliens exilés à Montréal pendant la dictature (1973-1989). La création de musiques de la résistance politique et la réception des auditeurs dans l’exil - Jordán González, Laura Francisca (Université de Montréal, 2010)
Keywords: Chiliens; Musique

Lorsque l'imaginaire migratoire rencontre les réalités de la migration: parcours de migrants volontaires et qualifiés de l'Afrique de l'Ouest au Québec - Michaud, Valérie (Université de Montréal, 2010)
Keywords: Africains

L’impact du loisir sur l’intégration sociale des minorités ethniques à Montréal: le cas des nouveaux arrivants originaires du Pérou - Murrugarra Cerna, Juan Carlos (Université de Montréal, 2010)
Keywords: Péruviens

Les trajectoires de l'intégration professionnelle des immigrants iraniens travaillant comme chauffeurs de taxi à Montréal - Namazi, Vahideddin (Université de Montréal, 2010)
Keywords: Iraniens

Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Number: 2
Keywords: Femmes; Travail

Le judaïsme à Montréal - Robinson, Ira (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Juifs

"We Started Over Again, We Were Young": Postwar Social Worlds of Child Holocaust Survivors in Montreal - Sheftel, Anna; Zembrycki, Stacey (Urban History Review / Revue d'histoire urbaine, 2010)
issued: 2010-23-00
Keywords: Clubs; Enfants; Juifs

Transition of Asylum Seekers from Shelters to Independent Living - Balyejjusa, Moses Senkosi (Université McGill, 2009)

Maternidad y migración: Entre recuerdos y pensares: Historias de vida de quince mujeres latinoamericanas que habitan en Montréal (Canadá) - Bedoya Idrobo, Luz Marina (Université de Montréal, 2009)
Keywords: Femmes; Latino-Américains

Facteurs linguistiques et sociolinguistiques de l'intégration en milieu multilingue: le cas des immigrants à Montréal - Calinon, Anne-Sophie (Université de Montréal, 2009)
Keywords: Langue

Les Chiliens au Québec. Immigrants et réfugiés, de 1955 à nos jours - Del Pozo, José (Boréal, 2009)
Keywords: Chiliens

Montréal-Nord 1980-2000. Aspects sociaux - Dupont, Antonin (Il était une fois... Montréal-Nord, 2009)
issued: 2009-23-00
Keywords: Haïtiens; Montréal-Nord; Noirs; Quartiers

L'histoire des quartiers d'immigration à Montréal: vers la construction d’une mémoire au-delà des territoires? - Germain, Annick (Migrance, 2009)
Number: 34
Keywords: Quartiers

La migration féminine qualifiée d’origine sud-américaine à Montréal: ressources culturelles et symboliques, et stratégies d’accès au marché de l’emploi - Guillen Castro, Maritza (Université de Montréal, 2009)
Keywords: Femmes; Travail

Agents of Change, Colours of Resistance: The Socio-Economic Integration of Filipina Live-In Caregivers in Montreal - Kapiga, Isabelle (Université Concordia, 2009)
Keywords: Femmes; Philippins

Les grandes tendances de l’immigration au Québec (1945-2005) - Linteau, Paul-André (Migrance, 2009)
Number: 34

Statut d'immigration, agentivité et référents identitaires: l'expérience migratoire d'immigrantes maghrébines - Morin, Marie-Pier (Université de Montréal, 2009)
Keywords: Femmes; Maghrébins

One (Wo)man’s Shopping is the Same (Wo)man’s history? Immigration, Advertisement and Consumption Patterns in the Greek community of Montreal 1960s-1970s - Pabst, Stavroula (Études canadiennes / Canadian Studies, 2009)
Number: 1
Keywords: Femmes; Grecs; Publicité

Diversité et pluralisme à Montréal: des perceptions, des faits - Paré, Sylvie (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)

Ségrégation urbaine et mobilité quotidienne, une perspective internationale: études de cas à Niamey, Puebla, Lyon et Montréal - Ravalet, Emmanuel (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2009)

Telling Lives, Making Place: The Narratives of Three Haitian Refugees in Montreal - Roux, Jonathan (Université Concordia, 2009)
Keywords: Haïtiens

L'envoi d'argent et de biens par les immigrants originaires de l'Amérique latine à Montréal: l'intimité économique au cœur des pratiques transnationales - Y-Lang Tran, Nathalie (Université de Montréal, 2009)
Keywords: Latino-Américains

La transmission de l'identité religieuse dans un contexte d'immigration: le cas de réfugiés tamouls hindous d'origine sri-lankaise à Montréal - Bradley, Mark (Université du Québec à Montréal, 2008)
Keywords: Sri Lankais

Facteurs associés aux conditions de logement des ménages immigrants au Canada. Étude de cas: le niveau de peuplement résidentiel des immigrants arrivés à Montréal en 1989 - Destiné, Fedner (Institut national de la recherche scientifique et Université de Montréal, 2008)
Keywords: Logement

L'envers de l'imaginé: la détresse comme discours socioculturel chez les migrants indiens de Montréal - Duclos, Vincent (Université de Montréal, 2008)
Keywords: Indiens

Acculturation Stress and Academic Performance among Foreign-Born Armenian Youth in the United States and Canada: An Exploratory Study - Karilian-Konyalian, Sarine (Université Concordia, 2008)
Keywords: Arméniens

Immigration and the Changing Social Geography of Large Canadian Cities - Ley, David; Germain, Annick (A Reader in Canadian Planning: Linking Theory and Practice, 2008)

Chinese Independent Immigrants in Montreal: Staying or Leaving? - Liu, Shi Yuan (Université Concordia, 2008)
Keywords: Chinois

Les Chinois de Paris et de Montréal: analyse comparative de deux communautés en situation d'immigration - Nicholls, Natalie C. (Canadian Review of Sociology / Revue canadienne de sociologie, 2007)
Le présent article consiste en une étude comparative de deux communautés chinoises en situation d'immigration dans deux pays différant par leur histoire et leur orientation politique: le Canada et la France. Bien qu'il n'en conclue ni à l'indépendance de ces communautés ni à la disparition du rôle des États nationaux, l'article relève maintee ressemblances sur le plan de la structure, de l'organisation et de l'économie interne reposant sur des réseaux ethniques transcendant les frontières.
Number: 3
Keywords: Chinois

Représentations culturelles et identité d'immigrants adultes de Montréal apprenant le français - Amireault, Valérie (Université McGill, 2007)
Keywords: Langue

Les immigrants roumains post-1989: vers une nouvelle communauté ethnoculturelle montréalaise? - Busuioc, Iulian (Université du Québec à Montréal, 2007)
Keywords: Roumains

L'importance des liens transnationaux dans la démarche migratoire des étudiants internationaux marocains à Montréal - Fortier, Marie-Ève (Université de Montréal, 2007)
Keywords: Maghrébins; Marocains; Étudiants

Les territoires fluides de l’immigration à Montréal ou le quartier dans tous ses états - Germain, Annick; Poirier, Cécile (Globe: revue internationale d’études québécoises, 2007)
Number: 1
Keywords: Quartiers

L'immigration arménienne à Montréal: caractéristiques et évolution de 1980 à 2005 - Laroche, Dominique (Université de Montréal, 2007)
Keywords: Arméniens

Les Québécois, les Juifs et l'immigration durant la Seconde Guerre mondiale - Rajotte, David (Bulletin d'histoire politique, 2007)
issued: 2007-23-00
Keywords: Guerre; Juifs

Modes de vie et modes de ville, activités et déplacements quotidiens à Montréal et Lyon - Ravalet, Emmanuel (Environnement Urbain / Urban Environment, 2007)
Number: 1, a61-a76
Keywords: Navettage

Stratégies identitaires et loisirs sportifs de groupe de récents immigrants chinois de première génération à Montréal - Zhang, Dan (Université du Québec à Trois-Rivières, 2007)
Keywords: Chinois

La situation résidentielle et les besoins en logement des immigrants récents dans la région métropolitaine de Montréal - Rose, Damaris; Germain, Annick; Ferreira, Virginie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2006)
Keywords: Logement

Être d'ici, de là-bas et d'ailleurs: l'expérience migratoire d'Africains établis à Montréal - Barry, Mamadou Cellou (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2006)
Keywords: Africains

La défense de l'identité bretonne dans un monde déterritorialisé - Ferry, Typhen (Université de Montréal, 2006)
Keywords: Français

Leonardo da Montreal: The Rhetoric of Italianità and the Canadian Post-Nation - Fratiloiu, Raluca Maria (Université Concordia, 2006)
Keywords: Centre Leonardo Da Vinci; Italiens

Langue et identité dans le Québec du XIXe siècle: une écriture triangulaire - Martineau, France; Avard, Annie (Envoyer et recevoir: lettres et correspondances dans les diasporas francophones, 2006)
Keywords: Famille; Langue

Route 117: une étude de la migration des jeunes abitibi-témiscamiens vers Montréal - Ouellette, Sébastien (Université de Montréal, 2006)

La mobilité internationale des étudiants universitaires: des facteurs d'influence à sa gestion, le cas de l'UQAM de 1993/94 à 2003/04 - Poupart, Isabelle (Université du Québec à Montréal, 2006)
Keywords: Université du Québec à Montréal; Étudiants

The Living Conditions of Older Latin American Immigrants in Montréal - Puga-Peña, Carmen (Université Concordia, 2006)
Keywords: Latino-Américains

La mobilité résidentielle des immigrants au Canada: les premiers mois - Renaud, Jean; Bégin, Karine; Ferreira, Virginie; Rose, Damaris (Canadian Journal of Urban Research / Revue canadienne de recherche urbaine, 2006)
Cet article examine un élément fondamental de l’établissement des nouveaux immigrants: leur établissement résidentiel. Plus spécifiquement on y étudie les facteurs qui déterminent la mobilité en début d’établissement par une analyse de la vitesse de sortie du tout premier logement au cours des six premiers mois suivant l’arrivée au Canada. Au nombre de ces facteurs seront tour à tour examinées certaines caractéristiques des ménages, certaines caractéristiques des individus, de même que leur effet différencié par région. Cette analyse sera réalisée sur les données de la première vague d’observation de l’Enquête sur l’Établissement des Immigrants au Canada (ELIC) réalisée environ après six mois de séjour (n=12 040). L’analyse est effectuée à l’aide de modèles de survie semi-paramétriques. Les résultats montrent que la mobilité résidentielle est tributaire de divers facteurs, tantôt associés aux caractéristiques des individus, tantôt reliés aux caractéristiques des ménages ou encore plus fortement au type de logement occupé. Cependant, les processus tentent à être indifférenciés selon la ville de résidence des nouveaux arrivants.
Number: 2
Keywords: Mobilité résidentielle

Immigrant Women Entrepreneurs in Montreal: Building Business and Lives - Simpson, Joni (Université Concordia, 2006)
Keywords: Femmes

Habiter, prendre pied, s'établir. Les commerçants et manufacturiers juifs de Montréal, 1918-1930 - Taschereau, Sylvie (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Juifs

Migration et développement: les transferts monétaires des immigrants haïtiens de la région métropolitaine de Montréal - Tremblay, Lisanne (Université de Montréal, 2006)
Keywords: Haïtiens

Les immigrants russophones à Montréal, une ou plusieurs communautés? Étude exploratoire - Billette, Amélie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2005)
Keywords: Russes

Les Madelinots à Verdun - Carbonneau, Pauline (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2005)
issued: 2005-21-00
Keywords: Quartiers; Verdun

Immigrants et travail à Montréal: la dynamique de l'établissement professionnel des dix premières années - Godin, Jean-François (Université de Montréal, 2005)
Keywords: Travail

The Scots of Montreal: a pictorial album - Marrelli, Nancy; Dardick, Simon (Véhicule Press, Musée McCord et St. Andrew's Society of Montreal, 2005)
Keywords: Écossais

Rencontres: La communauté portugaise de Montréal, 50 ans de voisinage / Encontros: A Comunidade Portuguesa de Montreal, 50 anos de vizinhança - Centre d'histoire de Montréal (Centre d'histoire de Montréal en collaboration avec le Carrefour des jeunes lusophones du Québec, 2004)
Keywords: Portugais

Your Roots Will Be Here, Away from your Home: Migration of Greek Women to Montreal 1950-1980 - Dounia, Margarita (Université McGill, 2004)
Keywords: Femmes; Grecs

Les immigrants sénégalais au Québec - Ndoye, Amadou (L'Harmattan, 2004)
Keywords: Sénégalais

Les Portugais, 50 ans à Montréal - Perpétua, Belmira (Les Intouchables, 2004)
Keywords: Portugais

Corps-fait-histoire dans le processus de mondialisation, de migration et d'insertion: parcours de femmes immigrantes péruviennes à Montréal - Rojas-Viger, Celia (Université de Montréal, 2004)
Keywords: Femmes; Péruviens

L'immigration juive européenne à Montréal dans les années d'après-guerre. Quelle identité, quelle mémoire, quelle intégration? - Spreter, Véronique (Université de Sherbrooke, 2004)
Keywords: Juifs

La grande Recrue de 1653 - Boileau, Gilles (Histoire Québec, 2003)
Number: 3
Keywords: Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de); Français; Histoire; Historiens; Le Royer de La Dauversière; Jérôme

L'impact de la conjoncture économique sur la situation en emploi d'une cohorte d'immigrants établie à Montréal - Fassi Fihri, Mohamed (Université de Montréal, 2003)

L'insertion urbaine des immigrants latino-américains à Montréal. Trajectoires résidentielles, fréquentation des commerces et lieux de culte ethnique et définition identitaire - Garcia Lopez, Magda (Institut national de la recherche scientifique et Université du Québec à Montréal, 2003)
Keywords: Chiliens; Guatémaltèques; Latino-Américains; Péruviens; Salvadoriens

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

Self-Identification Processes and their Reflection in the Language of Fourth-Wave Emigrants in Montreal - Migdissova, Svetlana (Université McGill, 2003)
Keywords: Langue; Russes

L’origine nationale et l’insertion économique des immigrants au cours de leurs dix premières années au Québec - Renaud, Jean; Piché, Victor; Godin, Jean-François (Sociologie et sociétés, 2003)
issued: 2003-21-00

Women and Ethnic Language Maintenance: A Study of Italian Immigrant Family Triads in Saint-Léonard, Montréal - Venditti, Rosa L. (Université Concordia, 2003)
Keywords: Italiens; Langue; Quartiers; Saint-Léonard

Acculturation et santé mentale: stress psychologique et satisfaction maritale chez des couples immigrants marocains à Montréal - Barampama, Mireille (Université de Montréal, 2002)
Keywords: Maghrébins; Marocains

L'immigration kabyle à Montréal: vivre sa berbérité au Québec - Beaumont, Valérie (Université de Montréal, 2002)
Keywords: Maghrébins

L'abbé Lionel Groulx et les conséquences de l'émigration canadienne-française aux États-Unis - Bélanger, Damien-Claude (Quebec Studies, 2002)
issued: 2002-21-00
Keywords: Groulx; Lionel

Communalisations ethniques post-migratoires: le cas des Turcs de Montréal - Bilge, Sirma (Université Sorbonne Nouvelle - Paris 3, 2002)
Keywords: Turcs

Les banlieues de l’immigration - Charbonneau, J; Germain, Annick (Recherches sociographiques, 2002)
Number: 2

Reconstruction identitaire des jeunes en contexte migratoire: cas des jeunes québécois d'origine haïtienne - Craan, George-Marie (Université du Québec à Montréal, 2002)
Keywords: Haïtiens

Trajectoires migratoires et espaces de sociabilité: stratégies de migrants de France à Montréal - Fortin, Sylvie (Université de Montréal, 2002)
Keywords: Français

Facteurs déterminants des styles parentaux des mères haïtiennes immigrantes à Montréal - Jean-Baptiste, Larissa (Université de Montréal, 2002)
Keywords: Famille; Femmes; Haïtiens

Itinéraires identitaires chez des immigrants libanais de Montréal: le cas de l'identité confessionnelle - Lebnan, Karim (Université de Montréal, 2002)
Keywords: Libanais

L’immigration féminine au Canada durant les années 1920: la mise en place d’une politique fondée sur le "genre" - Vallée, Marie-Hélène (Recherches féministes, 2002)
Number: 2
Keywords: Britanniques; Femmes

Differing Expectations: A Study of Chinese Children's Integration into Elementary School in Quebec - Zhongxiao, Chen (Université Concordia, 2002)
Keywords: Chinois; Enfants

Main-d'oeuvre immigrante et développement dualiste: l'économie canadienne au milieu du XIXe siècle - Seccareccia, Mario; Saint-Germain, Maurice (Histoire sociale / Social History, 2001)
Number: 68
Keywords: Britanniques

L’intégration des jeunes adultes migrants en milieu urbain au Québec - Desmarais, Danielle; Assogba, Yao; Fréchette, Lucie (Problèmes sociaux. Tome II: études de cas et interventions sociales, 2001)

Memory and Migration: Ethiopian Jews in Montreal - Djerrahian, Gabrielle (Université de Montréal, 2001)
Keywords: Africains; Juifs

Effect of Premigratory Exposure to Political Violence on the Social Anchorage of Refugees in Montreal - Drapeau, Aline (Université McGill, 2001)

Social Investment in Medical Forms: The 1866 Cholera Scare and Beyond - Curtis, Bruce (Canadian Historical Review, 2000)
Number: 3
Keywords: Choléra; Médecine; Épidémies

Immigrant Arabs and Immigrant Jews in Montreal: Their Social Interaction and Attitudes toward the Arab-Israeli Conflict - Abdo, Hadeel I. (Université Concordia, 2000)
Keywords: Arabes; Israéliens; Juifs

Acculturation, source d'information et comportement de consommation des immigrants chinois récents à Montréal (Québec, Canada) - Abhayavong, Krisnavanh (Université Laval, 2000)
Keywords: Chinois

Processus migratoire et santé mentale: étude de l'alcoolisme chez les immigrants et réfugiés salvadoriens à Montréal - Albanese, Caterina (Université de Montréal, 2000)
Keywords: Alcool; Salvadoriens

Le mouvement migratoire des jeunes au Québec. La reconfiguration du réseau social, un repère pour étudier le processus d’intégration - Assogba, Yao; Fréchette, Lucie; Desmarais, Danielle (Nouvelles pratiques sociales, 2000)
Number: 2

Le rôle des réseaux dans l'insertion économique d'une cohorte d'immigrants à Montréal - Chavez, Brigitte (Université de Montréal, 2000)
Keywords: Anglophones; Travail

Privacy in Homes of Shaamy Muslim Immigrants: A Study of Privacy Patterns in Single-Family Detached Homes and Townhouses of Middle-Class Immigrants in Montreal - Hallak, Mahmoud Essam (Université McGill, 2000)
Keywords: Musulmans; Syriens

La socialisation politique des réfugiés Chiliens de la première vague à Montréal - Hamel, Sonia (Université de Montréal, 2000)
Keywords: Chiliens

L’accueil et l’établissement de réfugiés Kosovars à Lyon et à Montréal, 1999-2000 - Helly, Denise; Bourgeois, Frédérique (Fonds d’action sociale auprès des immigrants et Mouvement pour l'intégration et la rétention en emploi, 2000)
Keywords: Kosovars

Creating Societies: Immigrant Lives in Canada - Hoerder, Dirk (McGill-Queen's University Press, 2000)

Les migrants américains et franco-américains au Québec, 1792-1940: un état de la question - Linteau, Paul-André (Revue d'histoire de l'Amérique française, 2000)
Number: 4
Keywords: Américains; Francophones

Shiftings of the Self: Towards a Deterritorialized View of Identity and Belonging. The Case of East and Central African-Asians in Canada - Matthews, Kim C. (Université Concordia, 2000)
Keywords: Africains; Indiens

The Experience of Adaptation in Canadian Society: A Case Study of Bangladeshi Families - Nazneen, Roksana (Université Concordia, 2000)
Keywords: Bengalis; Famille

Migrations intérieures des Québécois d’expression française, 1981-1986 et 1986-1991 - Paillé, Michel (Cahiers québécois de démographie, 2000)
issued: 2000-21-00
Keywords: Francophones; Mobilité résidentielle

Un transnationalisme familial: l'expérience des jeunes vietnamiens de Montréal - Richard, Éric (Université Laval, 2000)
Keywords: Vietnamiens

The Portuguese in Canada: From the Sea to the City - Teixeira, Carlos; Da Rosa, Victor M.P. (University of Toronto Press, 2000)
Keywords: Portugais